Deteksi Ancaman Keamanan Pada Server dan Jaringan Menggunakan OSSEC - Ronal Hadi; Yarmis Yuliana; Hanriyawan Adnan Mooduto (SOTVI - Society of Visual Informatics, 2022)
Cyber crimes can attack computer networks, infiltrate the network, retrieve confidential data and paralyze computer network systems. In overcoming the crimes that will occur, a system equipped with a firewall and an Intrusion Detection System (IDS) is needed. Firewall and IDS as network security features that can protect servers, networks, and block attacks. Firewall and IDS features can be implemented in OSSEC Tools. OSSEC is an open-source host-based intrusion detection system (HIDS) capable of performing log analysis, integrity checking, Windows registry monitoring, rootkit detection, time-based alerts, and active responses. OSSEC is capable of monitoring a single server or thousands of servers in server/agent mode